Career Choice and Attractiveness of Child and Adolescent Psychiatry as a Medical Specialty: A National French Questionnaire Survey - Revet, Alexis; Raynaud, Jean-Philippe; Marcelli, Daniel; Falissard, Bruno; Catheline, Nicole; Benvegnu, Grégoire (Frontiers in Psychiatry, 2021)
Context: The shortage of child and adolescent psychiatrists in France affects access to early interventions and mental health services but also impacts therapeutic practices and prescribing trends. The aims of this study were to describe factors associated with choosing child and adolescent psychiatry (CAP) as a career specialty and to assess the level of attractiveness of this discipline and its predictors. Methods: We generated a self-report questionnaire using a modified two-step Delphi approach. The survey was conducted from January 13th to February 16th 2020, and targeted French child and adolescent psychiatrists or psychiatrists mainly working with children and/or adolescents. We used a logistic regression model to assess the factors associated with the perception of CAP as attractive. A thematic qualitative analysis of the free comments section of the questionnaire was performed. Results: Of 863 doctors contacted by email, the response rate was 77.4% (668 respondents). Two-thirds of respondents were female and had an official specialization in CAP. One-third was aged between 31 and 40 years old. Main reasons for choosing to specialize in CAP were interest for work with children (64.2%), interest for psychotherapy (52.8%) and influence of an internship in CAP during medical studies (46.0%), although only one-third of respondents actually did an internship. Over half of respondents (57.3%) identified personal factors as implicated in their choice of CAP, mainly personal psychotherapy (22.2%) and personal trauma (14.4%). Although only 58.4% of respondents perceived CAP as attractive, 97.8% had no regret about their choice and 83.5% would make the same career choice today. A positive perception by respondents’ surroundings for choosing CAP at the time of the choice was associated to a perception of CAP as currently attractive by respondents (OR: 1.82; 95% CI: 1.27-2.60; p = 0.001). Conclusion: CAP is in crisis and faces many challenges in France, with an urgent need to redress its demographics. A vast majority of child and adolescent psychiatrists do not regret their choice and would choose the same specialty today. To increase its attractiveness, better visibility during medical school, enhanced academic recognition and increased remuneration seem promising.